JOURNALISM BASED ON ARTIFICIAL INTELLIGENT TECHNOLOGY (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-3-184-195The integration of the Internet in the media has contributed to the emergence of several new types of journalism, such as Robot Journalism, Drone Journalism, Data Science Journalism, etc. Formation of news materials, their attractiveness to the audience and the diversity of the fast dissemination ways of these materials in the society depend, first of all, on the development of advanced information technologies. The expansion of journalism based on advanced information technologies along with traditional journalism, the use of data mining, big data, and artificial intelligence in journalism have created new opportunities in this area. Although journalism of artificial intelligence ensures the requirements of the modern world and successfully solves the problems of the safety of journalists, the rapid collection and dissemination of information, it also has its drawbacks. The fact that journalism of artificial intelligence is far from the emotionality of the news transmitted, as well as the dynamic changes and excessive volumes of the news, indicate the change to be observed in the attitude of readers towards this news in the future. The aim of the study is to examine the influence of the Internet, which is a half century old, on the media as many other areas, as well as to identify existing problems in this area. To this end, the influence of artificial intelligence on modern journalism is studied and its opportunities and problems are identified. The advantages of journalism based on artificial intelligent over traditional one are specified. The study uses empirical and comparative analysis methods.Keywords: artificial intelligence, drone journalism, robotic journalism, social media, information security